Peningkatan kemampuan koneksi matematik peserta didik dengan menggunakan model pembelajaran means ends analysis (MEA) - Heryani, Yeni (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
This study aimed to see the increase of students’ mathematical connection by using model Means-Ends Analysis (MEA), and knowing how students’ learning motivation. The method used was an experimental pretest-posttest design. The study population were all students of class VIII SMP Negeri 3 Manonjaya as much as 121 students. Samples were taken by random technique become experiment class (30 students) and control class (30 students). The research instrument used test questions and questionnaires of mathematical connection. Data analysis concluded there was an increase in the students’ mathematical connection by using model Means-Ends Analysis (MEA), and students’ learning motivation of learning with Means-Ends Analysis (MEA) model was in high level.